Assessing the smart city: A review of metrics for performance assessment, risk assessment and construction ability assessment - Li He (Cogent Economics & Finance, 2023)
With the growing interest and concerns about the concept of smart city, assessing the smart city gains increasing attention from government planners, policy makers and related researchers around the world. This paper aims to provide a critical review of metrics involving national frameworks, institutional standards, and local reports, which focuses not only on the evaluation systems but also the assessing methodologies for assessing performance, risk and construction ability of smart cities. It is concluded that, most existing standards and research foci are on performance, and more attention needs to be paid to assessments of risk and construction ability. The former one suffers from the poor reliability and comparability resulting from massive indicators and unclear calculations, while the latter two are constrained by vague evaluation systems and insufficient method applications. Based on the comparison and discussion of the current research status, limitations and the future research directions, this research sheds light on better planning, monitoring and governance of smart cities. It also contributes to understanding and promoting the development of related research and even strategies or policies.
Keywords: 330; construction ability assessment; performance assessment; review; risk assessment; smart cities